Sistem Perkawinan Adat Lamaholot Dalam Perspektif Antropologi Di Desa Watodiri, Kecamatan Ile Ape, Kabupaten Lembata, Provinsi Nusa Tenggara Timur - Margaretha Nice O. Poli; Aliffiati Aliffiati; Ni Made Wiasti (Sunari Penjor : Jurnal of Anthropology, 2020)
Marriage in general is closely related to the two foundations of community life, namelyculture and religion. Culture is a very important traditional wedding ceremony, because traditional marriage will still exist in a cultured society. The traditional marriage system of the Lamaholot ethnic group has a hereditary culture, namely the traditional marriage of belis bala. Belis bala is a sacred aspect for the Lamaholot ethnicity, where men cannot undermine a woman's dignity. This study aims to determine: (a) The perspective of the younger generation on the belis bala in the Lamaholot ethnic traditional marriage system and (b) the inculturation of the church towards the traditional Laamaholot ethnic marriage system. Supported by Marcel Mauss' theory of reciprocity in compiling this research and the research model was made with the type of qualitative research, including data collection by observation, interviews, literature study and data analysis to process research results. The results of this study indicate the perspective of the younger generation, namely, there are some of them who feel heavy belis bala and want relief, but some others consider the traditional marriage system of belis bala as a challenge for them to be able to have their idol girl. They still want to maintain this traditional belis bala marriage system. The church sees this as a tradition that must be maintained. The church follows the regulations made by the village government for the preservation of the belis bala marriage system.